Evaluation of an information booklet for adolescents on depression: evidence from a randomized controlled study - Regine Primbs; Lisa Feldmann; Lucia Iglhaut; Antje-Kathrin Allgaier; Gerd Schulte-Körne; Ellen Greimel (BMC, 2023)
Abstract Background Adolescents with depression often show barriers to seek treatment offers due to various reasons, including limited knowledge about the manifestation of the disorder, its treatment options, or fear of stigmatization. Psychoeducational approaches might reduce these barriers by increasing depression literacy. The aim of the present randomized controlled study was to evaluate whether an innovative and age-appropriate evidence-based information booklet about youth depression increases depression-specific knowledge in adolescents with depression and is also appealing to the target group. Methods 50 adolescents with a history of depression (current/remitted) aged 12-18 years participated in the study including a pre-, post- and follow-up assessment. Participants were randomly assigned to one of two groups. The experimental group received a target group-specific information booklet about youth depression including seven subdomains. The active control group received an information booklet about asthma in youth that was highly comparable to the depression booklet in terms of format and length. Before and after reading, and at a four-week follow-up, we assessed knowledge about youth depression based on a questionnaire. Furthermore, participants evaluated the acceptability of the information booklets. Results Unlike the active control group, the experimental group showed a significant increase in depression-specific knowledge from pre to post and from pre to follow-up across all subdomains. This increase was evident in four subdomains ("symptoms", "treatment", "antidepressants", and "causes"). The overall reception of the information booklet about depression was positive and participants stated that they would recommend the information booklet about depression to their peers. Conclusion This is the first randomized controlled study to demonstrate that an information booklet about youth depression effectively imparts depression-specific knowledge to participants with a history of depression and shows high acceptance. Information booklets that are appealing and increase depression-specific knowledge might be a promising low-threshold and cost-effective approach to reduce barriers to treatment and raise awareness.